Emotions are the experiential glue of learning environments in the 21st century. (December 2020) - Graesser, Arthur C.
Abstract: This article comments on the five papers published in this special issue on understanding and measuring emotions in technology-rich learning environments . The articles identify a number of emotions that frequently occur in digital learning environments across different tasks, goals, populations, and subject matters. The Control Value Theory of achievement emotions unifies the research reported in the articles, whereas social emotions surface in contexts where there are significant social interactions, such as group learning or the training of medical students. The emotions that were detected and tracked in the reported studies rely on self-reports of learners and judges who observe them. This commentary identifies a number of limitations of the studies that will hopefully stimulate future research. Researchers are encouraged to collect (1) larger sample sizes, (2) longer interventions with learning technologies, (3) physiological, multimodal, and behavioral signatures of emotions to complement the subjective judgments, (4) more precise timing and transitions between emotions to uncover emotion dynamics, (5) assessments of nonlinear relations between variables, and (6) interventions designed to regulate and productively respond to learner emotions. Highlights: This article comments on the articles in this special issue on emotions in technology-rich learning environments. There are emotions that frequently occur across different tasks, goals, populations, and subject matters. The Control Value Theory of achievement emotions unifies the research but social emotions sometimes surface. This article recommends six directions for future research on emotions in technology rich environments.